Analysis of the social impact of research activities carried out in the area of selected social disciplines in Poland and in the UK - Lula, Paweł; Talaga, Magdalena; Dobranowska, Agata (Publishing House of Wroclaw University of Economics and Business, 2024)
The analysis of the social impact of research activity carried out in the area of selected social disciplines in the United Kingdom and in Poland was the main goal of the paper. The research process was conducted with the use of documents prepared for the evaluation procedures taking place in the United Kingdom in 2014 and in Poland in 2022 and presenting cases of the impact of research activity on society and the economy. This analysis, performed with the use of exploratory text analysis methods (particularly with the latent Dirichlet allocation model), allowed to identify topics and evaluate their significance in documents prepared by individual universities or groups of universities. A comparative analysis of the contents of descriptions was also performed. All the analyses presented in the paper were conducted by the authors with the use of computer programs written in the R language.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 52-65
Keywords: evaluation of the quality of research activity; social impact of research activity; topic modelling; Latent Dirichlet Allocation method; Research Excellence Framework